Inzerát - prostředek k vyhledání nového zaměstnání i nových zaměstnanců - Prouzová, Marie (Univerzita Pardubice, 1999)
In the present article, the sense and meaning of advertising for firms seeking for employers as for persons seeking employment is investigated. A general characteristic of structure of such insertions is done with pointing out the principal effectiveness defect there of short analysis of a copy of such advertising journal is presented.
Keywords: práce; zaměstnání; inzerce; zaměstnanci; hledání